2021
DOI: 10.3390/ijms221910799
|View full text |Cite
|
Sign up to set email alerts
|

What Are Reactive Oxygen Species, Free Radicals, and Oxidative Stress in Skin Diseases?

Abstract: Oxygen in the atmosphere is a crucial component for life-sustaining aerobic respiration in humans. Approximately 95% of oxygen is consumed as energy and ultimately becomes water; however, the remaining 5% produces metabolites called activated oxygen or reactive oxygen species (ROS), which are extremely reactive. Skin, the largest organ in the human body, is exposed to air pollutants, including diesel exhaust fumes, ultraviolet rays, food, xenobiotics, drugs, and cosmetics, which promote the production of ROS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 102 publications
(102 reference statements)
0
116
0
4
Order By: Relevance
“…It was found that ROS was closely related to the level of intracellular oxidative stress ( Apel and Hirt, 2004 ; Kattoor et al, 2017 ; Nakai and Tsuruta, 2021 ). Therefore, we evaluated the level of intracellular oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that ROS was closely related to the level of intracellular oxidative stress ( Apel and Hirt, 2004 ; Kattoor et al, 2017 ; Nakai and Tsuruta, 2021 ). Therefore, we evaluated the level of intracellular oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Free radicals may damage the skin by destroying lipid components of sebum and ceramides of the intercellular cement of the stratum corneum or by oxidation of polyunsaturated fatty acids of cell membrane phospholipids [ 17 , 18 ]. Free radicals, including 1 O 2 , directly damage the DNA and lipids of epidermal keratinocytes [ 19 ]. High ROS levels induce a complex cellular response in keratinocytes, with activation of the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) pathway.…”
Section: Oxs and Skin Ageingmentioning
confidence: 99%
“…High ROS levels induce a complex cellular response in keratinocytes, with activation of the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) pathway. NF-κB is a kappa light-chain synthesis promoter in B cells associated with cellular longevity (regulating the expression of telomerase genes, inflammation, angiogenic and anti-apoptotic factors, and cellular proliferation) and is involved in the development of skin diseases (psoriasis vulgaris, allergic dermatitis, and skin cancer) [ 19 , 20 ]. In human keratinocytes, oxidative stress caused by ROS can also lead to the activation of mitogen-activated protein kinase (MAPK) pathways.…”
Section: Oxs and Skin Ageingmentioning
confidence: 99%
“…The condition where the generation of ROS and RNS is particularly intense and the antioxidant mechanisms are insufficient is called oxidative stress. Free radicals are reactive with proteins, lipids and the genetic material of the cell [ 29 ]. Oxidative modifications of short peptides and large proteins lead to the impairment of the functions of individual biomolecules, affecting the conformation of the protein and the activity of enzymes [ 30 ].…”
Section: The Oxidant–antioxidant Balance In Human Organismsmentioning
confidence: 99%